Rogério Sganzerla : rastros de antropofagia no rosto de personagens do cinema marginal - Santana, Carlos Wagner Guterres (2021)
The presente work intends to investigate the traces of anthropophagy on the faces of characters from the Marginal Cinema demonstrated by the feature films of the Brazilian filmmaker Rogério Sganzerla: Sem essa, Aranha (1970) and Cobacabana mon amour (1970), that were produced in the midst of a turbulent scenario, aind in the middle of the Military Dictatorship, with emphasis on the neo-antropophagy and the Cinema Novo which, among other engaged movements, dialogued with the cinematography of the filmmaker. The research problem is fueled by the discussion about the presence of na antropophagy (Andrade, 1990; 2017) in the face (Deleuze, 2005; 2010; 2018) belonging ti the works, capable of influencing the production of meanings in the film. Hence the suspicion of the emergence of na anthropophagy thatreveals itself in small details of acts in wich the characters symbolically devour the opressor to increase their potential, in contrast to Cinema Novo. This question starts from the assumption that the characters feed on the enemy and regirgitate against him in planes of the face and in tracks left in the images that move the analyst to a more active and thinking position in front of the films. In addition to the theorists already mentioned, we will also work with the ideas of Pierre Clastres (1995), Beatriz Azevedo (2018), Antônio Candido (1964, 1976, 2006) e Guiomar Ramos (2008) for na undestanding of anthropophagy that permeates diferente ways of inserting the theme over time, with na emphasis on anthropophagic cinema, in addition to Fernão Ramos (1987), Jairo Ferreira (2000), Jean Claude Bernadet (1991, 2004), Eugênio Puppo (2012) e Ismail Xavier (2012) as well as testimonies from the direstors themselves, who help us to unravel the com complexity of Cinema Marginal. I also bring, in addition to Gilles Deleuze, Roberto Machado (2009) e Pedro Guimarães (2016a; 2016b), because this is an anthropophagy included in the characters‘ faces, so I tried to develop the concepts of affection-image, face and face to support the research analysis category. The methodology, in turn, will be based on studies of Walter Benjamin (1994) in the light of the concepto of trails, and if well sought and organized, they can composse a mosaic capable of reconfiguring historical impositions na injustices